Integrating Cross-sectoral Oversight and National Security in Combating Illegal Mineral Transport: A Policy Reformulation Approach - Djumarding, Arifuddin; Puluhulawa, Fenty U; Imran, Suwitno Yutye (Journal of Law and Policy Transformation, 2025)
This article discusses the integration of cross-sectoral oversight and the strengthening of national security in addressing illegal mineral transport via air routes. The study is motivated by the absence of explicit regulation governing the distribution of illegal minerals, creating legal loopholes despite prohibitions in the Mineral and Coal Law. This activity has led to significant economic losses, severe environmental degradation, and potential threats to national security. This research adopts a progressive normative-empirical approach with a policy-legal mapping method, combining regulatory analysis, authority mapping, and the incorporation of local values. The findings reveal weaknesses in oversight and coordination between agencies, as well as regulatory gaps and weak law enforcement. Impact analysis highlights economic losses, environmental damage, and risks to national security. This study emphasizes the need for integrated cross-sectoral oversight, enhanced coordination, and evidence-based policy reformulation to safeguard the distribution of strategic minerals. The findings are expected to form a foundation for effective policy implementation, supporting national economic, social, and security stability.